The Impact of International Pressures on Costs and Benefits of Voluntary Disclosures in Internationally Listed European Firms - Tze Yeung, Mok (2010)
With globalization of business, the information required by investors and debtors’ is becoming more complex and extensive. Several international organisations responsible for the establishment of risk disclosure guidelines are attempting to harmonize disclosure regulations across different financial industry segments that enable provision of sufficient and comparable disclosures that may improve economic resource allocations. Several researchers concluded that the multinational firms voluntarily disclosed more information than domestic firms. However, the motivation behind the difference of disclosure patterns has been rarely investigated. This paper postulates that understanding how international capital market pressures influence the cost and benefit trade-offs in internationally listed companies is necessary for the international organisation of securities commissions to harmonize the risk disclosure of companies listing on foreign stock exchanges. This study examined how international capital market pressures affect the financial markets variables to shape the choice of disclosure methods for interest rate exposure in 10-K filings of European non-financial firms listed in NYSE in 2009. The results showed that the market force variables -leverage level, firm size, external financing need and growth opportunities - shape the choice of disclosure method differently between internationally listed European firms and U.S. firms listed on domestic stock exchanges. The finding confirmed that multinational companies have their own system to trade off the costs and benefits of disclosures.